2020
DOI: 10.3389/fonc.2020.00859
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Metastatic Basal Cell Carcinoma of the Prostate: A Case Report and Literature Review

Abstract: Background: Primary basal cell carcinoma (BCC) is a rare prostate cancer. Currently, a standard treatment regime for BCC of the prostate is lacking and most patients have a poor prognosis. We reported on a patient with BCC of the prostate whose cancer metastasized after undergoing a radical prostatectomy and whose prognosis improved after treatment with etoposide. Case Presentation: A 62-year-old male with a history of seminoma was admitted complaining of intermittent gross hematuria for 1 month. Following a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…On the other hand, Dong et al . reported that a 62‐year‐old man with BCC showed multiple lung metastases 2 years after radical prostatectomy and adjuvant radiation 8 . The current 80‐year‐old patient showed 5% of Ki‐67 labeling index without other prostate malignant component and evident distant metastases so that we undertake no adjuvant radical treatment but close follow‐up.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, Dong et al . reported that a 62‐year‐old man with BCC showed multiple lung metastases 2 years after radical prostatectomy and adjuvant radiation 8 . The current 80‐year‐old patient showed 5% of Ki‐67 labeling index without other prostate malignant component and evident distant metastases so that we undertake no adjuvant radical treatment but close follow‐up.…”
Section: Discussionmentioning
confidence: 87%
“…Contrary to adenocarcinoma of the prostate, BCCs tend to metastasize viscerally to the liver, lung and bowel. Out of the 17 patients with advanced BCC of the prostate, 64.7% were diagnosed with liver metastasis [7,8 ▪ ,9–12].…”
Section: Review Of the Current Literaturementioning
confidence: 99%
“…The first case of BCCP was reported in 1974, and the total cumulativenumber of reported cases till date is about 140 ( 8 , 9 ). BCCP is usually considered to be insidious, but there are many reported cases of recurrence and metastasis ( 4 , 10 ). About 44% and 10% of patients experience recurrence and death due to metastasis, respectively ( 5 ).…”
Section: Discussionmentioning
confidence: 99%